Knowledge is light travellers in the Near East - Salahi, Katherine (Owbow Books, 2011)
For thousands of years travellers wandered to, and spread out through, Egypt and the Near East, seeking trade, adventure and knowledge. For centuries travellers to - and from - the Near East carried knowledge with them and then carried home the new knowledge acquired in the region. And knowledge, as the Arabic proverb states, is light